2013
DOI: 10.7567/jjap.52.090203
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Initial Unstable Contact Behaviors of Au-to-Au Microcontact under Low Contact Force for Micro- and Nano-Electromechanical System Devices

Abstract: The Au-to-Au micro/nano-contact behavior in unstable contact region during the initial stage of contact formation has been experimentally investigated under low contact force. The experimental results reveal that the asperity deformation process, which is conventionally observed in the stable region, could start from the early stage of contact formation in the unstable region. The fundamental mechanism for the instability of electrical conductance in the unstable region can be explained under a framework of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The switching behavior is similar to a two-level random telegraph signal (RTS) fluctuating between "on" and "off " states, which could be explained under the framework of trap-assisted tunneling process in the contamination film. 13) With the presence of the alien hydrocarbon at the metal surface, it is generally believed that the insulating alien layer needs to be broken before a stable contact can be formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The switching behavior is similar to a two-level random telegraph signal (RTS) fluctuating between "on" and "off " states, which could be explained under the framework of trap-assisted tunneling process in the contamination film. 13) With the presence of the alien hydrocarbon at the metal surface, it is generally believed that the insulating alien layer needs to be broken before a stable contact can be formed.…”
Section: Resultsmentioning
confidence: 99%
“…3,4) On the other hand, there is a growing demand to scale down the MEMS components towards the dimensions of sub-micrometers and nanometers, 9,10) in which the contact force could be drastically reduced to the range from less than 1 µN to around 50 µN. In such a low force region, electrical contact instability has been constantly observed in micro-contact tests, [11][12][13] and it is believed that the surface contamination plays an important role in determining the contact behavior for DC MEMS switches. 14,15) "Burn-in" process 16) under a contact voltage of 2-3 V or the "Schaltreinigung" procedure 17) (pre-switching with 50 V dc, 50 mA in nitrogen) was often applied to mitigate the effects of the surface contamination film and obtain appropriate resistance values; however, those methods can be destructive to miniature MEMS switches due to the high voltage/current level.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the mechanism behind the instabilities of electrical conductance during the critical period, Qiu et al 21,22 concluded that the thin contaminant films may play an important role in unstable contact behavior, and presented the trap-assisted electron tunneling mechanism for explaining the phenomena. It is possible that the different mechanical properties, elastic or rigid contact, are the reason for the inconsistent explanation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, the electrical conduction noise of ohmic-contact MEMS switches has not received much attention so far. On the other hand, the electrical contact instability under low contact force has been observed, [6][7][8] which could result in low frequency noise in MEMS devices. Scaling down of MEMS switches to sub-micrometer and nanometer region makes them more susceptible to unstable contact behaviors, due to the drastically reduced contact force.…”
mentioning
confidence: 99%
“…The switching behavior can be explained by the charge trapping and detrapping processes. 6 To better understand the physical origin behind the contact noise in low frequency region, the PSD of the contact voltage (V c ) fluctuations in the unstable region was obtained by conducting fast Fourier transform (FFT) for the time domain measurement results. Figure 3 shows the typical PSD as a function of frequency measured from samples in group A and group B.…”
mentioning
confidence: 99%